HPLC-DAD-ESI-QTOF-MS/MS profiling of Zygophyllum album roots extract and assessment of its cardioprotective effect against deltamethrin-induced myocardial injuries in rat, by suppression of oxidative stress-related inflammation and apoptosis via NF-κB signaling pathway. (30th January 2020) - Feriani, Anouar; Tir, Meriam; Gómez-Caravaca, Ana María; Contreras, María del Mar; Talhaoui, Nassima; Taamalli, Amani; Segura-Carretero, Antonio; Ghazouani, Lakhdar; Mufti, Afoua; Tlili, Nizar; Allagui, Mohamed Salah
Abstract: Ethnopharmacological relevance: Zygophyllum album is widely used to treat many cardiovascular diseases (CVDs) and as anti-inflammatory plant. Aim of the study: This study aimed to investigate the mechanism of the potential protective effects of Zygophyllum album roots extract (ZARE) against myocardial damage and fibrosis induced by a chronic exposure to deltamethrin (DLM) in rats. Materials and methods: Bioactive compounds present in ZARE were analyzed by HPLC-DAD-ESI-QTOF-MS/MS. In vivo, DLM (4 mg/kg body weight), ZARE (400 mg/kg body weight) and DLM with ZARE were administered to rats orally for 60 days. Biochemical markers (LDH, ALT, CK, CK-MB and cTn-I) were assessed in the plasma by an auto-analyzer. Pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) were evaluated by a sandwich ELISA. NF-κB was quantified at mRNA levels by real time PCR. Heart tissue was used to determine cardiac oxidative stress markers (MDA, PC, SOD, CAT, and GPx). Masson's Trichrome (MT) and Sirius Red (SR) stainings were used for explored fibrosis statues. Results: Phytochemical analysis using HPLC-DAD-ESI-QTOF-MS/MS revealed the presence of twenty six molecules including phenolic compounds and saponins. ZARE significantly improved the heart injury markers (LDH, ALT, CK, CK-MB and cTn-I), lipid peroxidation (MDA), protein oxidation (PC), antioxidant capacity (SOD, CAT, and GPx), and DNA structure, which were altered by DLM exposure. Moreover, ZARE cotreatment reduced the expressions of NF-κB, decreased plasmatic pro-inflammatory cytokines concentration (TNF-α, IL-1β and IL-6), and suppressed the myocardial collagen deposition, as observed by Sirius Red and Masson's Trichrome staining. Conclusion: ZARE ameliorated the severity of DLM-induced myocardial injuries through improving the oxidative status and reducing profibrotic cytokines production. The ZARE actions could be mediated by downregulation of NF-κB mRNA. Graphical abstract: Image 1